MiR-1297 suppresses pancreatic cancer cell proliferation and metastasis by targeting MTDH. (August 2018) - Chen, Zili; Ma, Yifei; Pan, Yaozhen; Zhu, Haitao; Yu, Chao; Sun, Chengyi
Abstract: Dysregulation of miR-1297 has been detected in various human cancers, and miR-1297 can function as either an oncogene or tumor suppressor. However, the role of miR-1297 in pancreatic adenocarcinoma has not been previously reported. Here, we investigated miR-1297 expression in pancreatic cancer and the role it plays in the development and metastasis of pancreatic adenocarcinoma. In the present study, MiR-1297 and metadherin (MTDH) expression in pancreatic cancer tissue was detected using quantitative real-time PCR (qRT-PCR) and western blot methods. The CCK-8 assay and EdU incorporation assay were used to analyze the impact of miR-1297 and MTDH on cell proliferation. Flow cytometric and Hoechst 33342 staining methods were used to explore how miR-1297 and MTDH affect cell apoptosis. The Transwell assay and scratch wound healing assay were used to analyze cell migration and invasion capabilities. The dual-luciferase assay was used to confirm that miR-1297 targets MTDH . Here, we found that miR-1297 expression was decreased in pancreatic adenocarcinoma tissues, while MTDH expression was increased in those tissues. Furthermore, western blot and dual-luciferase assay results confirmed that MTDH was a direct target of miR-1297. Additionally, overexpression of miR-1297 or knockdown of MTDH suppressed BxPC-3 and PANC-1 cell proliferation, and upregulation of miR-1297 or suppression of MTDH promoted BxPC-3 and PANC-1 cell apoptosis. Finally, BxPC-3 and PANC-1 cell migration and invasion abilities were suppressed by either overexpression of miR-1297 or downregulation of MTHD. In conclusion, our results suggest that miR-1297 inhibits the growth and metastasis of pancreatic adenocarcinoma by downregulating MTDH expression, and the miR-1297/MTDH pathway is a potential target for treating pancreatic adenocarcinoma. Highlights: miR-1297 expression was decreased in pancreatic adenocarcinoma tissues. MTDH expression was increased in pancreatic adenocarcinoma tissues. miR-1297 targets MTDH . miR-1297/MTDH pathway is a potential target for treating pancreatic adenocarcinoma.